Educational and socio-economic inequalities of pre-university Brazilian population: A view from the ENEM data - Rodrigo Travitzki; Maria Eugénia Ferrão; Alcino Pinto Couto (Arizona State University, 2016)
Based on an intergenerational perspective, the study examines the mitigation of the inequalities in the distribution of education, taking into consideration the relationships between educational achievements and socio-demographic attributes such as socioeconomic status and race/color. The research uses ENEM data and the observations spans from 2009 to 2012. In order to examine the educational inequalities, the analysis explores the Gini coefficient, the Lorenz curve and multilevel modeling data for the year 2012. Using the level of education, as well as the ENEM's test scores, the evidence suggests the reduction of intergenerational inequalities in the distribution of education. In addition, the results indicate that educational performance is sensitive to socio-spatial and race-related variables. The multilevel analysis allowed the decomposition of the variance of educational outcomes at the pre-university level and for different UF's. Such approach reveals that the variability of results at the intra-municipal level is greater than at the inter-municipal setting. Moreover, empirical evidences indicates the existence of substantial performance variability among schools, suggesting that either schools or municipalities are relevant units for educational policies. The reduction of these disparities must be considered a priority issue. Additional research related to determinants of school effect, considering intra and extra-school dimensions, and educational effectiveness-oriented policies is needed.